2017
DOI: 10.1002/jez.b.22753
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation in Anuran Limbs: Constraints and Novelties

Abstract: Anurans have three primary types of locomotion: walking, jumping, and swimming. Additionally, they may dig, climb, grasp, etc. All adult anurans have four limbs, with four fingers on the hands and five toes on the feet. We summarized and updated knowledge on the interspecific variation within anuran limbs, then discuss how developmental constraints (e.g., in size) and novelties may have influenced anuran diversification through the locomotion. We analyze morphological variation from limb bud stages up to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 105 publications
3
28
0
Order By: Relevance
“…Ruhi et al, 2014;Heino et al, 2015;Spasojevic et al, 2016), while limited dispersal ability imposed by limb morphology and physiological restrictions (risk of desiccation) compromise long-distance anuran dispersal (Wells, 2010;Amado et al, 2019). Differences in life history, morphology, and locomotion mode directly affect trait-environment relationships and species turnover dominance (Fabrezi et al, 2017), as observed in our study. According to our predictions, distance between ponds mostly influenced variation patterns in traits associated with habitat exploitation in arboreal species -head shape, eye position and, particularly, limb length.…”
Section: Complex Relations Between Traits and Environment In Anuranssupporting
confidence: 66%
“…Ruhi et al, 2014;Heino et al, 2015;Spasojevic et al, 2016), while limited dispersal ability imposed by limb morphology and physiological restrictions (risk of desiccation) compromise long-distance anuran dispersal (Wells, 2010;Amado et al, 2019). Differences in life history, morphology, and locomotion mode directly affect trait-environment relationships and species turnover dominance (Fabrezi et al, 2017), as observed in our study. According to our predictions, distance between ponds mostly influenced variation patterns in traits associated with habitat exploitation in arboreal species -head shape, eye position and, particularly, limb length.…”
Section: Complex Relations Between Traits and Environment In Anuranssupporting
confidence: 66%
“…Frog limbs develop in a proximal‐distal direction (Fabrezi et al. 2017), so the increased evolutionary rates we found may indicate that similar developmental constraints influence anuran limb evolution.…”
Section: Discussionmentioning
confidence: 65%
“…Limb development in frogs also follows a proximal‐distal direction (Fabrezi et al. 2017), but unlike in amniotes, limb formation occurs later and is decoupled from organogenesis in the phylotypic stage, relaxing constraints against changes to the number of distal elements (Galis et al. 2001; Irie and Sehara‐Fujisawa 2007).…”
mentioning
confidence: 99%
“…These structures have been studied using several approaches in anurans: descriptive (e.g. Gaupp, ; Parsons, ; Devanesen, ; Slater, ; Emerson, ; Nussbaum, ; de SĂĄ & Trueb, ; Trueb et al, ; Hoyos, ; Guayasamin, ; Manzano & Barg, ; Avilan & Hoyos, ; Ponssa, , ; Chaparro, Pramuk & Gluesenkamp, ; Lehr & Trueb, ; Maglia, PĂșgener & Mueller, ; Manzano et al, ; Soliz & Ponssa, ), ontogenetic (Olson, ; Vickaryous & Olson, ; Ponssa et al, ; Abdala & Ponssa, ; Vera & Ponssa, ; Vera et al, ; Ponssa & Abdala, ; Soliz & Ponssa, ; Abdala et al, ; Fabrezi, Goldberg & Chuliver Pereyra, ), and functional (Emerson, , ; Clarke, ; Olson, ; Manzano & Barg, ). In some studies, characters derived from sesamoids are used in phylogenetic analyses (Laurent, , , ; Nussbaum, ; Cannatella & Trueb, ; Scott, ; Wiens et al, ; Fabrezi, ; BĂĄez, Moura & GĂłmez, ), or optimized in phylogenies (Olson, ; Ponssa et al, ; Soliz & Ponssa, ).…”
Section: Sesamoids In Tetrapodamentioning
confidence: 99%